ASPEK SOSIAL EKONOMI TUMPANGSARI HUTAN DI KESATUAN PEMANGKUAN HUTAN (KPH) CIAMIS WILAYAH DAERAH ALIRAN SUNGAI (DAS) CITANDUY - Rachman Effendi; Akub J Abdurachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
One of planting pattern in reforestation that has proved to be successful is taungya system. The advantage gained by the farmers are especially in the fulfilment of food need in the short term.The average income of farmers from taungya system in KPH Ciamis, Citanduy catchment area, is I47.526,- rupiahs per year per share area (0.219I hectare) or 28.5% of farmer total income.Variables that significantly influence the income from taungya system (YI) are production facility expenditure (XI), labour cost (X2), and share area (X6). The relationship is shown by linear regression model YI = 154,4588 + l,2791 XI + I,8254 X2 + 0,0214 X6 (R2 = 0,8388).Farmers income level from taungya system has positively influenced the main plants. The regression model that shows the relationship between farmer income and base plane area is shown by the equation Y2 = 0,3557 + 0,05I3 YI (R2 = 0,6801) at 99% confidence level.